2018
DOI: 10.1063/1.5028257
|View full text |Cite
|
Sign up to set email alerts
|

Integrating AlInN interlayers into InGaN/GaN multiple quantum wells for enhanced green emission

Abstract: Significant enhancement in green emission by integrating a thin AlInN barrier layer, or interlayer (IL), in an InGaN/GaN multiple quantum well (MQW) is demonstrated. The MQWs investigated here contains 5 periods of an InGaN QW, a 1 nm thick AlInN IL, and a 10 nm thick GaN barrier grown by metalorganic chemical vapor deposition. To accommodate the optimum low-pressure (20 Torr) growth of the AlInN layer a growth flow sequence with changing pressure is devised. The AlInN IL MQWs are compared to InGaN/AlGaN/GaN M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 43 publications
(89 reference statements)
0
13
0
Order By: Relevance
“…The improvement of IQE has played a key role in LED development. Specifically, the IQE of the InGaN LEDs have been improved by using the large overlap quantum well concept or the new active material concept [17,18,19,20]. Generally, LEDs should be driven at a high current density to obtain higher light output power (LOP), which also inevitably generates a large portion of heat [21].…”
Section: Introductionmentioning
confidence: 99%
“…The improvement of IQE has played a key role in LED development. Specifically, the IQE of the InGaN LEDs have been improved by using the large overlap quantum well concept or the new active material concept [17,18,19,20]. Generally, LEDs should be driven at a high current density to obtain higher light output power (LOP), which also inevitably generates a large portion of heat [21].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that further optimization or more creative IL schemes could lead to further gains. For example, recently it has been shown that ILs formed from AlInN can be used, and these structures exhibit efficiency gains that are similar to AlGaN ILs …”
Section: Challenges and Solutionsmentioning
confidence: 99%
“…One approach for higher efficiency longer wavelength InGaN LEDs that has produced record efficiencies at green gap wavelengths is the use of AlGaN interlayers in the multiple quantum well (MQW) active layer. [87,96,[121][122][123][124][125][126][127] This is most interesting in the green and red because of demonstrated record external quantum efficiencies of 25% at 550 nm [125] and 2.5% at 608 nm. The AlGaN interlayer (IL) is grown on top of the InGaN quantum well as shown in Figure 5a.…”
Section: Solutions For Higher Efficiencies Of Green and Red Emittersmentioning
confidence: 99%
See 1 more Smart Citation
“…To power this hypothesized space station, a high-efficiency solar cell based on the combination of III-V groups solar cells like GaInP, GaInAs, AlGaAs, InP, and GaAs might be used in the form of multijunction solar cells (MJSC). The unique electronic structure of III-V based materials had long been known to have a wide range of applications, such as in quantum wells LED [18][19][20][21][22][23], laser [24], sensors [25], and also solar cells [26][27][28][29][30][31]. Those III-V groups solar cells are known for their ability to withstand harsh conditions in the outer space, such as energetic particles and high temperature [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%